Growth and 4-ethylphenol production by the yeast Pichia guilliermondii in grape juices - Malfeito-Ferreira, Manuel (2009)
The behavior of Pichia guilliermondii strains producing high levels of 4-ethylphenol in synthetic media was studied in wines and grape juices. These strains lost their viability and did not produce 4-ethylphenol after 24 hr of inoculation in red wines with ethanol adjusted to 10 or 12 % (v/v) and pH 3.5, in the absence of free sulphite. Under the same conditions, at 12 % (v/v) ethanol, growth of Dekkera bruxellensis was observed. When grown in single culture in grape juices, selected strains of P. guilliermondii produced high levels of 4-ethylphenol. In mixed grape juice fermentations with Saccharomyces cerevisiae, P. guilliermondii began to die after starter inoculation at 107 cfu/mL and did not produce 4-ethylphenol. Low starter inoculation rates (102 cfu/mL) added 72 hr after P. guilliermondii inoculation resulted in high production of 4-ethylphenol. In conditions mimicking cold pre-fermentative maceration processes, at 10ºC for 72 hr, P. guilliermondii did not grow, while at 25ºC growth attained a 104 fold increase. At this temperature, addition of 200 mg/L potassium metabisulfite after grape crushing did not eliminate P. guilliermondii inoculated at 104 cfu/mL in grape juice of pH 3.57. The possibility that high levels of 4-ethylphenol in wines are due to the activity of P. guilliermondii should be mostly related with uncontrolled growth in contaminated grape juices before starter inoculation. In wines, its ability to produce 4-ethylphenol seems to be much lower than that of D. bruxellensis.